EFFECTS OF GENDER AND AGE ON REACTION TIME DURING VISION COACH TASK - Register, Joshua (East Carolina University, 2016)
This study examined the effects of gender and age on reaction time during visual-motor tasks on a dynamic light board, Vision Coach[trademark], which is a prospective tool to be used for occupational therapy evaluation and/or intervention. As part of the study, normative data was gathered and established for the Vision Coach tool, specifically for the Full Field 60 task (i.e., reacting to 60 red dots as fast as possible), as normative data has yet to be published for clinical use. A cross over design was used to compare the relationship of age and gender as it relates to reaction time performance on the Vision Coach. One hundred twenty-one younger and older adults from the university and the surrounding community participated in the study. Data analysis revealed significant differences (p[less than or equal to]0.001) between reaction time of younger and older adults. The average trial time difference between the two age groups was 17±1.08 seconds. While data analysis revealed differences in reaction time between genders, this difference was non-significant. Due to the integration of complex skills related to driving that are also needed to engage in this task, it was discussed as it related to the skills needed for scanning and reacting to the driving environment. These results suggest that the Vision Coach may serve as a beneficial screening or intervention tool for drivers undergoing driving assessments.
Keywords: Vision Coach; Full Field 60; Psychomotor Performance; Motor Vehicles; Vision, Ocular; Reaction Time